Ratings of perceived exertion among standard treadmill protocols and steady state running - Glass, S. C.; Whaley, M. H.; Wegner, M. S. (International Journal of Sports Medicine, 1991)
The purpose of this study was to determine if differences exist in ratings of perceived exertion (RPE) at a predetermined relative heart rate between two standard treadmill protocols and steady state exercise in a field setting. Thirty healthy male (N=15) and female (N=15) volunteers were maximally tested using the standard Bruce and a modified Balke (3.0 mph with 2.5% grade each two minutes) protocols. Each subject was randomly assigned to one treadmill protocol first, and then completed the second test forty-eight hours later. Within forty-eight hours following the second treadmill test, all subjects completed a field exercise trial consisting of an 800-m run. During the field trial an investigator paced each subject to an individualized target heart rate (75% maximal heart rate reserve) calculated from the treadmill tests. The total exercise time for the field trial was 4:31 ±0:22 and 5:36 ±0:47 min for the males and females, respectively. During the last 50 m of the field trial, RPE values were recorded. Comparisons of the rating of perceived exertion at the target heart rate (RPE at THR) were made using a 2-way (Gender × Trials) ANOVA with repeated measures across trials. There was a significant gender × trials interaction for RPE at THR, with males reporting significantly higher values during the treadmill tests as compared to the females (BRUCE = 13.5 ± 1.6 vs 12.2 ±1.8; BLAKE =15.9 ±2.3 vs 13.7 ±2.4). There was no difference noted between genders for RPE at THR during the field trial. A within-gender analysis of RPE at THR across trials revealed a similar pattern for both males and females: Balke > Bruce > field trial (p < 0.01). The greater RPE at THR seen during the Balke test may be due to: (1) the local fatigue and discomfort associated with the excessive treadmill incline employed during the Balke protocol, (2) the extended period of time necessary to complete a maximal effort during the Balke protocol, and/or (3) the more frequent reporting of RPE during a shorter stage duration test. These data suggest that when testing healthy individuals, for the purpose of providing an exercise prescription, using a treadmill protocol with modest increases in intensity per stage yields greater RPE's at a given heart rate as compared to a more abrupt, non-steady state protocol. In addition, RPE at THR values obtained during a standardized treadmill test may not accurately reflect the perception of effort at the same relative heart rate in the exercise training setting.